Interdisciplinary Approaches to Semiotics - Lopez-Varela Azcarate, Asuncion (IntechOpen, 2017)
This volume stresses the contemporary relevance of semiotics. The introductory chapter shows how the collection of papers emphasises crossings at the material level of physical reality as well as in their semio-cognitive and cultural implications, questioning the delimitation of interdisciplinary borders between the social sciences and humanities and STEM disciplines. The volume shows how semiotics continues to provide a framework for emerging knowledge traditions without completely disregarding its past. Through explorations in fields as wide apart as ecological psychology and visualisation systems, by finding correspondences between the arithmetic of music and cosmic energies or between the pedagogic significance of images and habitat facilities, as well as using investigation tools ranging from the mathematical representation of concepts to science education, this book addresses multifarious aspects and implications of culture and cognition, standing convincing proof that semiotics is as alive, productive and scholarly useful as ever.